2003
DOI: 10.1016/s0306-4522(03)00560-8
|View full text |Cite
|
Sign up to set email alerts
|

The proprotein convertase PC2 is involved in the maturation of prosomatostatin to somatostatin-14 but not in the somatostatin deficit in Alzheimer's disease

Abstract: Abstract-A somatostatin deficit occurs in the cerebral cortex of Alzheimer's disease patients without a major loss in somatostatin-containing neurons. This deficit could be related to a reduction in the rate of proteolytic processing of peptide precursors. Since the two proprotein convertases (PC)1 and PC2 are responsible for the processing of neuropeptide precursors directed to the regulated secretory pathway, we examined whether they are involved first in the proteolytic processing of prosomatostatin in mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 59 publications
4
18
0
Order By: Relevance
“…Less neuronal NRDc might, for example, affect neuropeptide levels in AD brains. In this way, NRDc might contribute to the dysregulation of dynorphins in AD (Yakovleva et al 2007) and, possibly, to the elevated levels of the isoform somatostatin-28 Winsky-Sommerer et al 2003), which appear in parallel to the well-documented general somatostatin deficit in AD (Rossor et al 1984;Beal et al 1987;Mouradian et al 1991;Dournaud et al 1995). Although there is only little, if any, overlap of NRDc and somatostatin-28 immunoreactive nerve cell bodies in human brain (Bernstein et al 2007), a reduced somatostatin-28 metabolising function of NRDc (Csuhai et al 1998) cannot be ruled out in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Less neuronal NRDc might, for example, affect neuropeptide levels in AD brains. In this way, NRDc might contribute to the dysregulation of dynorphins in AD (Yakovleva et al 2007) and, possibly, to the elevated levels of the isoform somatostatin-28 Winsky-Sommerer et al 2003), which appear in parallel to the well-documented general somatostatin deficit in AD (Rossor et al 1984;Beal et al 1987;Mouradian et al 1991;Dournaud et al 1995). Although there is only little, if any, overlap of NRDc and somatostatin-28 immunoreactive nerve cell bodies in human brain (Bernstein et al 2007), a reduced somatostatin-28 metabolising function of NRDc (Csuhai et al 1998) cannot be ruled out in AD.…”
Section: Discussionmentioning
confidence: 99%
“…The lower limit of sensitivity was 12.5 pg/tube and the intra-and interassays of variation were of 3% and 4.9%, respectively. A SRIH RIA was performed as previously published (25). The sensitivity threshold of the assay was 0.5 pg/tube and the intra-and interassay coefficients of variation were below 10%.…”
Section: Hormone Assaysmentioning
confidence: 99%
“…34,35 Furthermore, it is well known that somatostatin performs crucial roles in the brain and that its decrease represents a pathological feature of AD, even though this reduction is not accompanied by an alteration of proteolytic processing of peptide precursors. 36 Although the mechanism that couples alterations of the somatostatinergic system to AD remains unclear, recently, it has been shown that somatostatin regulates β-amyloid metabolism through the modulation of neprilysin proteolytic activity. 19,23,24 In this work, we show for the first time that the neuropeptide somatostatin is not only a novel substrate of IDE but also a modulator of its activity toward a FβA peptide, corresponding to the 10-25 amino acid sequence of the Aβ(1-40), which displays a behavior quite similar to that observed for the intact Aβ(1-40) (see Fig.…”
Section: Ide Is a Znmentioning
confidence: 99%